The Authority of Policy: Transitioning from Traditionalist to Modernist Moderate in Saudi Arabia - Roro Fatikhin; Syihabuddin Qalyubi; Subaidi Subaidi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
Saudi Arabia has long been known for its rigidity and conservative image, influenced by the close relationship between the kingdom and religious leaders. However, in the twenty-first century, Saudi Arabia began to embrace a more modern and moderate direction, moving away from conservatism and traditionalism. This shift is attributed to the Saudi reform policy, known as Saudi Vision 2030, which has had a significant impact on the country's social, cultural, and religious aspects. As a result, the authority of the Saudi kingdom has strengthened, while the authority of religious leaders has diminished. The research utilizes Plato's theory of authority and the modernization theory of Evsey Domar and Roy Harrod, combined with a socio-political approach, to analyze the policy authority of the Saudi kingdom and its impact on other sectors. The findings of the research indicate that the 21st century marked the beginning of socio-cultural changes in Saudi society, spearheaded by King Salman ibn Abdul Aziz and his son, Muhammad ibn Salman. The authority they wielded allowed for transformative ideas that aimed to modernize the conservative country. The introduction of Saudi Vision 2030 has brought about significant changes, including a shift towards modernist policies in social, political, and religious matters. Examples of these changes include increased freedoms for women, decreased reliance on oil in economic policies, the development of tourist attractions and entertainment venues, and greater equality in education and employment opportunities.